Apert syndrome: a case report in pediatric dentistry - Contreras Linares, Rocío (2011)
Apert syndrome accounts for 5% of all craniosynostosis syndromes and shows a prevalence of 1 in 60000 live births. Is one of the five craniosynostosis syndromes associated with single mutations in the Fibroblast Growth Factor Receptor 2 (FGF-R2) gene, with chromosomal localization at 10q26. The purpose of this paper was to describe a case of Apert syndrome, show Pediatric dentistry managementand discuss their craniofacial features in an 8-year-old boy who presented Craniosynostosis, turribrachycephaly, syndactylies of the hands and feet, with multiple intraoral features.